Principal Component Analysis of Climate Variables (Temperature and Wind) at Erbil Weather station (Eurasian Journal of History, Geography and Economics, 2023)
Climatic elements have a great influence in reflecting the prevailing climate in any region, which is related to the geographical location and the dominance of other natural influences such as the factor of altitude or sea level drop, and proximity to water bodies. And the geographical location of the region in relation to latitude and longitude, which has a great influence in determining the nature of the climate everywhere on the surface of the earth, and in our topic here, which is about the influence of climatic factors on the nature of the climate that governs the province of Erbil and its impact on the inhabitants of the region and their way of life and the work they do in This climate rule frame is dependent on a weather station reading. in Erbil Governorate in the northern region of Iraq